2006
DOI: 10.1155/ijmms/2006/49279
|View full text |Cite
|
Sign up to set email alerts
|

Null controllability of a nonlinear population dynamics problem

Abstract: We establish a null controllability result for a nonlinear population dynamics model. In our model, the birth term is nonlocal and describes the recruitment process in newborn individuals population. Using a derivation of Leray-Schauder fixed point theorem and Carleman inequality for the adjoint system, we show that for all given initial density, there exists an internal control acting on a small open set of the domain and leading the population to extinction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…The proof of this Carleman inequality follows the method of [10] for parabolic equation. In [13] we have established similar Carleman inequality, but without the particular form of the constants.See also [2]. For completeness and in order to justify the particular form of the constants λ 0 and s 0 (λ) we give the entire proof in the appendix, at the end of the paper.…”
Section: A(a−a)t(t −T) and ϕ(T A X) = E λψ(X)mentioning
confidence: 78%
“…The proof of this Carleman inequality follows the method of [10] for parabolic equation. In [13] we have established similar Carleman inequality, but without the particular form of the constants.See also [2]. For completeness and in order to justify the particular form of the constants λ 0 and s 0 (λ) we give the entire proof in the appendix, at the end of the paper.…”
Section: A(a−a)t(t −T) and ϕ(T A X) = E λψ(X)mentioning
confidence: 78%
“…Related approximate and exact controllability issues have also been studied in Ainseba [2], Ainseba and Langlais [5], Ainseba and Iannelli [4], Traore [24], Kavian and Traore [17]. Using a direct approach, the approximate controllability by birth or boundary control is studied in Yu, Guo and Zhu [27].…”
Section: 4)mentioning
confidence: 99%
“…Concerning the nonlinear population dynamics model, a null controllability result was established by Ainseba, B. and Iannelli, M. by means of Kakutani fixed point theorem (Ainseba & Innanelli, 2003). Using a derivation of Leray-Schauder fixed point theorem and Carleman inequality for the adjoint system, Traoré, O. showed that for all given initial density, there exists an internal control acting on a small open set of the domain and leading the population to extension in (Traoré, 2006). Sawadogo, S. and Mophou, G. (Sawadogo & Mophou, 2012) gave a null controllability result for population dynamics model with constraints on the state when the age of the population belongs to (γ, A) for any γ > 0.…”
Section: Introductionmentioning
confidence: 99%